Modern physical organic chemistry - Anslyn, Eric V., 1960- (University Science, 2006)
Making explicit the connections between physical organic chemistry and critical fields such as organometallic chemistry, materials chemistry, bioorganic chemistry and biochemistry, this book escorts the reader into an area that has been thoroughly updated in recent times.